1996
DOI: 10.1007/s002849900083
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aeromonas hydrophila Strains of Clinical, Animal, and Environmental Origin Expressing the O:34 Antigen

Abstract: A collection of Aeromonas strains of different origins were characterized for isolates expressing the O:34 somatic antigen. Of over 200 strains tested, approximately 14% belonged to serogroup O:34 with >85% of these strains identified as A. hydrophila regardless of source. A subset of 14 A. hydrophila O:34 strains were further analyzed for a number of structural and pathogenic features. Most O:34 strains expressed similar whole-cell protein profiles with regards to minor bands, but major band differences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Furthermore, live attenuated vaccines such as aroA mutant and transposon Tn916-generated mutant have been reported to confer significant protection against homologous A. hydrophila challenge [25,26]. However, it is well known that A. hydrophila is very heterogeneous biochemically and serologically, which is the biggest obstacle in developing effective commercial vaccine against A. hydrophila [23,27]. To prevent future disease outbreaks caused by the highly virulent West Alabama 2009 isolates of A. hydrophila, an attenuated vaccine AL09-71 NþR specifically targeting A. hydrophila AL09-71 was developed [28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, live attenuated vaccines such as aroA mutant and transposon Tn916-generated mutant have been reported to confer significant protection against homologous A. hydrophila challenge [25,26]. However, it is well known that A. hydrophila is very heterogeneous biochemically and serologically, which is the biggest obstacle in developing effective commercial vaccine against A. hydrophila [23,27]. To prevent future disease outbreaks caused by the highly virulent West Alabama 2009 isolates of A. hydrophila, an attenuated vaccine AL09-71 NþR specifically targeting A. hydrophila AL09-71 was developed [28].…”
Section: Introductionmentioning
confidence: 99%
“…By using the typing system of Sakazaki and Shimada (19), several important Aeromonas serogroups have been defined. These include serogroup O:11, which is responsible for serious invasive clinical infections such as septicemia, meningitis, and peritonitis (13), and serogroup O:34, which is responsible for human wound infections such as myonecrosis and epizootic outbreaks of septicemia in goldfish (12,17).…”
mentioning
confidence: 99%
“…Initial electrophoretic studies on aeromonad LPS demonstrated three main patterns, the first being a major ladder-like pattern that is often seen in the enterobacteria and is associated with smooth (S) LPS. The second is characterised by the presence of some O-antigen chains demonstrating a homogeneous pattern and the third a rough (R) or semi-rough pattern in which no O-antigen is present and there is usually one main band present representing the core (Khashe, Hill, & Janda, 1996;Kokka, Vedros, & Janda, 1990;Tso & Dooley, 1995). A number of aeromonad LPS O-antigen serogroups have been shown to be regulated by heat, these being O:13, O:33, O:34 and O:44.…”
Section: Lipopolysaccharidementioning
confidence: 99%